2022
DOI: 10.1371/journal.pone.0262963
|View full text |Cite
|
Sign up to set email alerts
|

Construction of computer model for enterprise green innovation by PSO-BPNN algorithm and its impact on economic performance

Abstract: The present work aims to analyze the elements that affect corporate green technology innovation and investigate a method suitable for predicting and evaluating corporate performance. First, the elements of green technology innovation and their relationships are analyzed and explained. Then, the Complex Adaptive System (CAS) theory is introduced. On this basis, a computer model for the driving mechanism system of corporate green technology innovation is constructed on the Recursive Porus Agent Simulation (Repas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, they explored the impact of green product innovation on enterprise performance, arguing that green innovation brings cost not only efficiency but also profitability to firms and that the pursuit of green product innovation can better contribute to enterprise performance in terms of both cost efficiency and profitability even in a dynamic environment [21][22][23][24][25]. There is rich research literature exploring green innovation from different theoretical perspectives, and studies from a strategic flexibility perspective have found that green innovation can contribute to improved enterprise performance [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they explored the impact of green product innovation on enterprise performance, arguing that green innovation brings cost not only efficiency but also profitability to firms and that the pursuit of green product innovation can better contribute to enterprise performance in terms of both cost efficiency and profitability even in a dynamic environment [21][22][23][24][25]. There is rich research literature exploring green innovation from different theoretical perspectives, and studies from a strategic flexibility perspective have found that green innovation can contribute to improved enterprise performance [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Particle Swarm Optimization (PSO) is a heuristic search technique with simple implementation, high global search capability, and superior performance [ 34 ]. PSO simulates the foraging behavior of birds and is used to solve optimization problems [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The basic idea of PSO improving the BP algorithm is to analyze the fitness of each individual in the group to the environment, find the best location in the area where the individual is located, and use the cooperation and information sharing of each individual in the group to move to the best location in the area. The algorithm treats each individual in the swarm as a particle without volume and mass, and each particle flies in a given search space at a certain speed, thus realizing a dynamic iterative update [ 25 , 26 ].…”
Section: An Optimized Bp Neural Network Modelmentioning
confidence: 99%